Hubungan Senam Hamil dengan Kualitas Tidur Ibu Hamil Trimester III - Fadilah; Sari Tanberika, Fajar; Ruspita, Rika; Yanti, Rifa (Sinar : Jurnal Kebidanan, 2026)
Background: As pregnancy enters the third trimester, physical and psychological changes occur. These conditions cause pregnant women to experience complex complaints, such as discomfort that affects sleep quality. One solution to address this discomfort is prenatal exercise Purpose: The purpose of this study was to determine the relationship between prenatal exercise and sleep quality among pregnant women in their third trimester at the Alai Community Health Center in West Tebing Tinggi District. Methods: This study employed a descriptive analytical design. The research method used was cross-sectional. The population in this study was 50 people. The sampling method used was purposive sampling. The sample consisted of 34 pregnant women, selected using the Slovin formula. Data collection in this study used a questionnaire, distributing a series of written questions to respondents to obtain information. The study period was from October to December. Data were analyzed using the Wilcoxon test. Results: The results of this study were analyzed using the Wilcoxon sign rank test. Results: The mean value of sleep quality before the intervention was 5.15 and experienced a change in the mean value after the intervention to 1.75. The results of the analysis using the Wilcoxon sign rank test showed a p value of 0.000 <α = 0.05. Conclusion: The conclusion of this study is that there is a relationship between pregnancy exercise and the quality of sleep of pregnant women at the Alai Community Health Center, West Tebing Tinggi District